2019
DOI: 10.3390/molecules24071197
|View full text |Cite
|
Sign up to set email alerts
|

Co-Existence of Hypertensive and Anti-Hypertensive Constituents, Synephrine, and Nobiletin in Citrus unshiu Peel

Abstract: A single herb can contain multiple constituents with diverse bioactivities. We found that the extract of Citrus unshiu peel (CUP), induced abnormal vasoconstriction responses on the freshly isolated rat aortic rings in vitro. CUP stimulated the vasoconstriction alone, and it suppressed the phenylephrine-stimulated vasoconstriction. We studied the reasons behind this abnormal vasoconstriction pattern. Major constituents of CUP were determined and evaluated for their vaso-activities. Notably, synephrine, a contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…These data suggest that citrus unshiu peel is an agonist of OX1R. In an aqueous extract mixture of NYT, the main ingredients of citrus unshiu peel were hesperidine, nobiletin, tangeretin, heptamethoxyflavone, naringin, and synephrine (53)(54)(55). Some studies on blood pharmacokinetics indicated that these ingredients are absorbed into the blood in humans after oral administration (56,57).…”
Section: Discussionmentioning
confidence: 94%
“…These data suggest that citrus unshiu peel is an agonist of OX1R. In an aqueous extract mixture of NYT, the main ingredients of citrus unshiu peel were hesperidine, nobiletin, tangeretin, heptamethoxyflavone, naringin, and synephrine (53)(54)(55). Some studies on blood pharmacokinetics indicated that these ingredients are absorbed into the blood in humans after oral administration (56,57).…”
Section: Discussionmentioning
confidence: 94%
“…Relative contents of different bioactive chemical components also lead to different pharmacological activities. For instance, a previous study has mentioned that the relative contents of synephrine and nobiletin coexisted in citrus, significantly affecting the vasoconstriction pattern since synephrine and nobiletin competitively blocked or activated the same contractile targets (Kim et al., 2019 ). Therefore, the differences in the phytochemicals of CER, CREA, and CFR were further clarified in this study, which might provide the chemical basis for explaining the different pharmacological activities and rational development of them.…”
Section: Discussionmentioning
confidence: 99%
“…the intestines [3][4][5]. However, some animal experiments and clinical results indicated that the decoctions or aqueous extracts of Zhishi and Zhiqiao probably connoted some pharmacological effects contrary to synephrine and N-methyltyramine [6].For example, (1) transiently or inapparently raising, or sometimes even declining the blood pressure [7,8]; (2) various cardiovascular protections [9,10]; (3) an excitatory effect to the in vitro and in vivo uteruses of pregnant and nonpregnant rabbits [11]; (4) a two-way regulating effect on gastrointestinal smooth muscle, namely not only exciting the gastrointestinal tract and enhancing its peristalsis, but also reducing the tension of gastrointestinal smooth muscle and relieve spasm [12]. These facts showed that there are probably some other ingredients with cholinergic or anti-cholinergic activities in the decoctions or aqueous extracts of Zhishi and Zhiqiao although some reports indicated that citrus flavonoids and essential oil should play a certain role in these complicated functions [13][14][15].…”
Section: Of 25mentioning
confidence: 99%